Comparative production analysis of three phlebovirus nucleoproteins under denaturing or non-denaturing conditions for crystallographic studies. - Violaine Lantez; Karen Dalle; Rémi Charrel; Cécile Baronti; Bruno Canard; Bruno Coutard (Public Library of Science (PLoS), 2011)
Nucleoproteins (NPs) encapsidate the Phlebovirus genomic (-)RNA. Upon recombinant expression, NPs tend to form heterogeneous oligomers impeding characterization of the encapsidation process through crystallographic studies. To overcome this problem, we set up a standard protocol in which production under both non-denaturing and denaturing/refolding conditions can be investigated and compared. The protocol was applied for three phlebovirus NPs, allowing an optimized production strategy for each of them. Remarkably, the Rift Valley fever virus NP was purified as a trimer under native conditions and yielded protein crystals whereas the refolded version could be purified as a dimer. Yields of trimeric Toscana virus NP were higher from denaturing than from native condition and lead to crystals. The production of Sandfly Fever Sicilian virus NP failed in both protocols. The comparative protocols described here should help in rationally choosing between denaturing or non-denaturing conditions, which would finally result in the most appropriate and relevant oligomerized protein species. The structure of the Rift Valley fever virus NP has been recently published using a refolded monomeric protein and we believe that the process we devised will contribute to shed light in the genome encapsidation process, a key stage in the viral life cycle.